2017
DOI: 10.1007/s13205-017-0754-1
|View full text |Cite
|
Sign up to set email alerts
|

Using an artificial neural network to predict the optimal conditions for enzymatic hydrolysis of apple pomace

Abstract: The enzymatic degradation of lignocellulosic biomass such as apple pomace is a complex process influenced by a number of hydrolysis conditions. Predicting optimal conditions, including enzyme and substrate concentration, temperature and pH can improve conversion efficiency. In this study, the production of sugar monomers from apple pomace using commercial enzyme preparations, Celluclast 1.5L, Viscozyme L and Novozyme 188 was investigated. A limited number of experiments were carried out and then analysed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The neutral network model has been trained and built on the features of 62 corn stover samples through rolling learning-prediction approach. The selection of the most appropriate parameters for ANN modeling is considered of paramount importance for prediction of the hydrolysis process [ 27 ]. In the present work, to test the prediction capabilities of the neural network model, the predicted values obtained from the model are compared with the experimental values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The neutral network model has been trained and built on the features of 62 corn stover samples through rolling learning-prediction approach. The selection of the most appropriate parameters for ANN modeling is considered of paramount importance for prediction of the hydrolysis process [ 27 ]. In the present work, to test the prediction capabilities of the neural network model, the predicted values obtained from the model are compared with the experimental values.…”
Section: Resultsmentioning
confidence: 99%
“…The agreement in measured and net-simulated slopes and intercepts indicated the trained networks satisfactorily predicted the saccharification results based on the features of corn stover. It has been reported in literature that ANNs are flexible as new data can be added anytime giving fitting [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…An optimized ANN model was developed based on hydrolysis conditions to maximize sugar yields. Gama et al (2017) established an ANN applied to predict the best conditions to maximize glucose and reduce sugar yields from enzymatic hydrolysis of apple pomace using as inputs: temperature, pH, enzyme, and substrate loadings (Gama et al 2017). In this case, the training and testing data set contained minimal fluctuations, which showed that enzymatic hydrolysis could benefit significantly from ANN technologies because it does not require specific feedstock composition details as input (Pomeroy et al 2022).…”
Section: Processes Of the Biochemical Biorefinerymentioning
confidence: 99%
“…The initial rise in TRS levels could be attributed to the requirement of an optimum amount of substrate proportional to enzyme levels present in the reaction mixture. The decrease in the hydrolysis yield at high substrate loading might occur due to adsorption of enzymes on to unproductive sites in the biomass, mass transfer limitations, or end-product inhibition of enzyme due to higher sugar levels (Gama et al 2017).…”
Section: Biomass Saccharificationmentioning
confidence: 99%